RESEARCH OF KC CHARACTERISTIC OF SUSPENSION SYSTEM OF VEHICLE WITH RIGID-FLEXIBLE COUPLING MODEL - LI Cheng; ZHANG HongTao; JIANG NengHui (Jixie qiangdu)
The comprehensive performance of suspension directly affects the handling stability and riding comfort of the vehicle. The suspension performance of a domestic vehicle was verified. By using ADAMS/car software, the front suspension model with flexible stabilizer bar subsystem and the rear suspension model with flexible torsion beam subsystem are established to form the suspension system of vehicle with rigid-flexible coupling model. The displacement and force were applied to the suspension system respectively. The dynamic and elastic kinematics analysis were carried out, and the wheel alignment parameters under different characteristics were obtained. The simulation results show that the simulation values were basically consistent with the real vehicle K＆C test data. The comprehensive performance of the suspension of this model was more optimized than that of the standard model. At the same time, through the rolling acceleration, understeering and car rolling three aspects, the steady-state rotary road test was conducted to further verify that the steady-state characteristics of the vehicle meet the design requirements and have good motion characteristics.